A 1‐year randomized controlled trial of a nutritional blend to improve nutritional biomarkers and prevent cognitive decline among community‐dwelling older adults: The Nolan Study. Issue 1 (28th September 2022) - Giudici, Kelly V.; Guyonnet, Sophie; Cantet, Christelle; de Souto Barreto, Philipe; Weiner, Michael W.; Tosun, Duygu; Boschat, Corina; Hudry, Julie; Andrieu, Sandrine; Vellas, Bruno; Schmitt, Jeroen A. J.; ,
Abstract: Introduction: This study aimed to test the efficacy of a nutritional blend (NB) in improving nutritional biomarkers and preventing cognitive decline among older adults. Methods: A 1‐year randomized, double‐blind, multicenter, placebo‐controlled trial with 362 adults (58.6% female, mean 78.3 years, SD = 4.8) receiving an NB or placebo. Erythrocyte ω‐3 index and homocysteine concentrations were primary outcomes. Other outcomes included Patient‐Reported Outcomes Measurement Information System (PROMIS) Applied Cognition‐Abilities, composite cognitive score (CCS), Cognitive Function Instrument (CFI) self‐assessment and study partner, hippocampal volume (HV), and Alzheimer's disease signature cortical thickness (CT). Results: A total of 305 subjects completed the follow‐up. Supplementation increased ω‐3 index and decreased homocysteine, but did not affect CCS, CFI self‐assessment, HV, and CT. Placebo improved and treatment did not change PROMIS at 1 month. Intervention showed a positive effect on CFI study partner. Discussion: Although improving nutritional biomarkers, this 1‐year trial with a multi‐nutrient novel approach was not able to show effects on cognitive outcomes among older adults.